Embodied Genres, Typified Performances, and the Engineering Design Process. (October 2021) - Weedon, Scott; Fountain, T. Kenny
Using rhetorical genre theory, the authors theorize the engineering design process as a type of embodied genre enacted through typified performances of bodies engaged with discourses, texts, and objects in genre-rich spaces of design activity. The authors illustrate this through an analysis of ethnographic data from an engineering design course to show how a genred repertoire of embodied routines is demonstrated for students and later taken up as part of their design work. A greater appreciation of the interconnection between genre and design as well as the role of typification in producing embodied genres can potentially transform how writing studies conceives of and teaches both design processes and genres in technical and professional communication settings.